2004
DOI: 10.1038/sj.bjc.6602235
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen receptor status, pathological complete response and prognosis in patients receiving neoadjuvant chemotherapy for early breast cancer

Abstract: The aim of this study was to ascertain if oestrogen receptor (ER) status predicts for pathological complete response (pCR) to neoadjuvant chemotherapy in operable breast cancer, and the effects of pCR on survival. Using a single-institution database, 435 patients were identified, who received neoadjuvant chemotherapy for operable breast cancer and were eligible for the analysis. Patients whose tumours were ER negative were more likely to achieve a pCR than patients who were ER positive (21.6 vs 8.1%, Po0.001).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
134
2
21

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(173 citation statements)
references
References 28 publications
16
134
2
21
Order By: Relevance
“…Patients with ER-negative tumors are more likely to achieve a pCR after neoadjuvant chemotherapy than those with ER-positive tumors. 26 This also was demonstrated in a retrospective review, which indicated that the pCR rate in studies with anthracycline-based chemotherapies ranged from 1.2% to 14.3% in patients with hormone receptor-positive tumors and from 7.1% to 54.5% in patients with hormone receptor-negative tumors. However, in that analysis, the HER2 status of tumors was not known.…”
Section: Evaluating the Efficacy Of Neoadjuvant Therapymentioning
confidence: 77%
“…Patients with ER-negative tumors are more likely to achieve a pCR after neoadjuvant chemotherapy than those with ER-positive tumors. 26 This also was demonstrated in a retrospective review, which indicated that the pCR rate in studies with anthracycline-based chemotherapies ranged from 1.2% to 14.3% in patients with hormone receptor-positive tumors and from 7.1% to 54.5% in patients with hormone receptor-negative tumors. However, in that analysis, the HER2 status of tumors was not known.…”
Section: Evaluating the Efficacy Of Neoadjuvant Therapymentioning
confidence: 77%
“…One of the oldest (validated) prognostic and predictive factor is the ER. It was demonstrated that pCR is more likely to occur in patients with ER negative than ER positive disease [30][31][32][33]. Therefore, preoperative chemotherapy may not be the most appropriate preoperative approach for patients with ER positive disease.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that the pathological complete remission (pCR) rate was significantly higher following PCT for patients with tumors not expressing estrogen (ER) and progesterone receptor (PgR), compared with the receptor positive cohort [4][5][6]. Regardless of the significantly higher incidence of pCR for patients with ER and PgR absent disease, the 5-year disease-free survival (DFS) was significantly worse for this cohort compared with the low/positive expression cohort in several studies [5][6][7][8]. In these studies analyses were performed based on a so-called 'receptor-negative grouping', which combines receptor-absent disease with that expressing low receptor levels, and 'receptor positive grouping' which combines all patients with tumors expressing ER and/or PgR in C10% of the cells.…”
Section: Introductionmentioning
confidence: 99%